Managing business relationships in uncertainty: An Indonesian traditional banana supply chain study - Obeth, Ernita (Curtin University, 2016)
The purpose of the study is to explore how members of traditional supply chains treat uncertainty and manage their relationships in responding to uncertainty. Using case study analysis on dyads across the supply chain, it was found that mechanisms such as tolerance, postponed payment, and money lending allow supply chain members to maintain long-term, reliable relationships and thus, gain competitive advantage. The results show how uncertainty is managed in an informal economy in Indonesia.